Analisis Kointegrasi & Vector Error Correction Model Faktor Penentu Pajak Daerah Kabupaten Bandung Barat - Heryana, Toni; Solikin, Ikin; Fitriani, Indah (Program Studi Akuntansi FPEB UPI, 2018)
Abstract. Planning for local tax in Distric of West Bandung Barat still incremental and ignores the factors that influence it. This study aims to build a model for estimating local tax by using a cointegration regression model on regional expenditure, inflation, and gross regional domestic product on regional tax revenues during 2010 - 2015 in Distric of Bandung Barat. The results of the study show simultaneously and partially the regional expenditure variables, inflation, and gross regional domestic products have an influence on local tax revenues. The cointegration regression analysis also shows that there is a long-term balance between each variable of regional expenditure, inflation, and gross domestic product on tax revenues which means that changes in each independent variable to the dependent variable occur in a very long period. Cointegration regression can be used as a tool to estimate local tax revenues in the long run. Keywords: Local Tax, Co-Integration, VECM Regional Expenditure, Inflation, PDRB Abstrak. Perencanaan pajak daerah pada Kabupaten Bandung Barat masih bersifat incremental dan mengabaikan faktor – faktor yang mempengaruhinya. Penelitian ini bertujuan membangun model estimasi pajak daerah dengan menggunakan model regresi kointegrasi atas belanja daerah, inflasi, dan produk domestik regional bruto terhadap penerimaan pajak daerah selama tahun 2010 – 2015 di Kabupaten Bandung Barat. Hasil penelitian menunjukkan secara simultan dan parsial variabel belanja daerah, inflasi, dan produk domestik regional bruto memiliki pengaruh terhadap penerimaan pajak daerah. Analisis regresi kointegrasi juga menunjukkan adanya keseimbangan jangka panjang antara masing – masing variabel belanja daerah, inflasi, dan produk domestik bruto terhadap penerimaan pajak yang diartikan bahwa perubahan masing – masing variabel independen terhadap variabel dependen terjadi dalam periode yang sangat lama. Regresi kointegrasi dapat digunakan sebagai alat untuk mengestimasi penerimaan pajak daerah dalam jangka panjang. Kata Kunci: Pajak Daerah, Kointegrasi, VECM, Belanja Daerah, Inflasi, PDRB